An Investigation on Rural Community Development Measures and Community Development: A Study of Yorro Local Government Area of Taraba State, Nigeria - Orjianimaku Micheal Chinedu; Nwosu Chinedu Everest (Researchparks Publishing, 2023)
This study investigates the linkage between rural community development measures and community development in Yorro Local Government Area of Taraba State, Nigeria. To actualize this objective, two hypotheses were formulated in the study. The survey research design was adopted for the study. A sample size of 399 was adopted from the population of the study using Taro Yamane formula for sample size determination. The purposive sampling technique was adopted to select the respondents that were drawn from the districts in Yorro Local Government Area. The data collected from the field were presented using frequency distribution tables and simple percentages while the chi-square statistical tool was used to test the hypothesis formulated in the study. The test hypothesis reveals among others that, there is significant relationship between the provision of agricultural inputs and increased food production in Yorro Local Government Area. The study concludes that rural community development measures in the form of providing agricultural inputs and basic or infrastructural amenities by government at all levels to the inhabitants of rural communities is a panacea towards increasing food production and instigating structural development in rural communities. The study recommends among others that, Taraba State Government should increase investment on agricultural inputs such as the provision of fertilizers, pesticides and insecticides to farmers as well as train and re-train the farmers in modern methods in farming techniques through collaboration with research institutes. By so doing, there would be increase in food production in rural communities and beyond.